ARABIC LANGUAGE LEARNING DEVELOPMENT IN THE USE OF JIGSAW METHOD AT MADRASAH ALIYAH AL-WASHLIYAH CLASS X. TEMBUNG PERCUT SEI TUAN - Muhajir, Muhammad Rizky (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
This study aims to improve Arabic language learning in using the Jigsaw method at Madrasah Aliyah Al-Washliyah in class Ten Tembung Percut Sei Tuan. The formulation of the problem in this study is how to improve the Jigsaw learning method in enrichment of student learning outcomes on Arabic vocabulary in class X at Madrasah Aliyah Al-Washliyah Tembung Percut Sei Tuan. Is there an increase in student learning outcomes in enrichment taught with the Jigsaw learning method. This class action research was conducted through 2 cycles which included planning, implementation, observation and reflection activities. While to determine the ability of students, researchers use student worksheets given to students. The population in this study was the entire class X of 26 students. From the research results, it can be seen that the results of the initial test (pre-test) in class X the percentage of classical completeness was obtained 54.38% (6 students). After giving teaching actions through the Jigsaw learning method, the student learning outcomes test I percentage of classical completeness was obtained 61.73% (20 students). While after improvement from cycle I, in cycle II, the results of learning test II (Post-test) obtained the percentage of classical completeness obtained 89.80%. From the results of this class action research, the researcher concluded that there was an increase in student learning outcomes by using the Jigsaw learning method in class X Madrasah Aliyah Al-Washliyah Tembung Percut Sei Tuan